Tumour-associated macrophages: Relation with progression and invasiveness, and assessment of M1/M2 macrophages in canine mammary tumours. (April 2018) - Monteiro, L.N.; Rodrigues, M.A.; Gomes, D.A.; Salgado, B.S.; Cassali, G.D.
Highlights: Tumour-associated macrophage (TAM) counts are higher in more aggressive histotypes of canine mammary tumors (CMTs). TAM counts are related to various clinicopathological parameters and overall survival in CMTs. Macrophages subpopulations are predominantly of M1 type in benign CMTs and of M2 type in malignant CMTs. Abstract: Macrophages represent a major component of the overall leucocyte population within neoplasms and are important for tumour behaviour in several cancers in human beings. However, little information regarding their role in canine mammary tumours (CMTs) is available. The aim of this study was to address the potential role of tumour-associated macrophages (TAMs) in CMTs. TAMs in CMTs excised from 82 female dogs were quantified at high power (400× magnification) and categorised as low (≤50) or high (>50) TAM counts. Higher TAM counts were associated with clinical stage ( P < 0.001), tumour type ( P = 0.016), tumour size ( P = 0.013), vascular invasion ( P = 0.031), lymph node metastasis ( P = 0.003), high proliferation rates ( P = 0.009), vascular microdensity ( P = 0.008), invasive tumour profile ( P = 0.002) and worse prognosis ( P = 0.018; hazard ratio = 0.283). Almost all macrophages infiltrating malignant tumours with high TAM counts expressed CD206 (macrophage mannose receptor 1), while all benign tumours were infiltrated by macrophages expressing inducible nitric oxide synthase (NOS2), suggesting a phenotypic shift from classically activated macrophage (M1) subpopulations towards alternatively activated macrophage (M2) subpopulations in malignant tumours. A triple staining pattern revealed mixed M1/M2 profiles in some tumours, thus characterising an intermediate state. The results indicate that TAMs are associated with more aggressive types of mammary cancer in dogs.